Attitudes and Awareness towards Environmental Management and its Impact on Environmental Management Practices (EMPs) of SMEs in Sri Lanka - Weerasiri, Sudath (Journal of Social and Development Sciences, 2012)
The main objective of this paper was to investigate whether there is an association amongst SMEs’ attitudes, awareness on environmental issues and their environmental management practices. A questionnaire-based survey was chosen to obtain the information on attitudes, awareness and environmental management practices of SMEs. The questionnaire was developed to find out SMEs’ current environmental management practices as well as their attitudes and awareness on environmental issues. The associations amongst attitudes, awareness and environmental practices for waste, energy, and the environment were investigated by calculating correlation coefficient. These analyses revealed that there is no significant association between attitudes and awareness or attitudes and environmental management practices. Attitudes appear to be remaining positive even where awareness is limited. Managers/owners who expressed rather more positive attitudes appear no more likely introduce environmental management practices for their organizations than managers/owners with less or negative attitude.